2014
DOI: 10.26477/idj.v36i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Traumatized Anterior Teeth among 13-15 Years Old Intermediate School Students in Hilla City, Babylon Governorate- Iraq

Abstract: Background: Dental trauma in children and adolescents is a common public health problem in all societies and the prevalence of these injuries has increased during the past few decades. Injury of permanent teeth may cause cosmetic, functional and psychological problems to the patient. The aim of this study was to investigate the prevalence and severity of traumatized anterior teeth in relation to age, gender, type of injury and type of occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(14 reference statements)
2
3
1
Order By: Relevance
“…Children with simple enamel fracture was seen to be the highest followed by those with enamel and dentin fracture, the same finding was recorded in previous studies on permanent teeth (13,14) The upper maxillary central incisors were the most common involved teeth with dental trauma. The same finding was reported by other studies (14,32) , this could be explained by fact that the prominent position of the maxillary incisors in the face was responsible for their more frequent involvement in fracture than the lower teeth (33) .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Children with simple enamel fracture was seen to be the highest followed by those with enamel and dentin fracture, the same finding was recorded in previous studies on permanent teeth (13,14) The upper maxillary central incisors were the most common involved teeth with dental trauma. The same finding was reported by other studies (14,32) , this could be explained by fact that the prominent position of the maxillary incisors in the face was responsible for their more frequent involvement in fracture than the lower teeth (33) .…”
Section: Discussionsupporting
confidence: 86%
“…The difference in the prevalence of traumatic dental injury could be attributed to differences in ages between studied populations. Results demonstrated that males were more affected by dental trauma than females and the difference was statistically highly significant, this result could be explained by fact that males may tend to be more active and had more energetic action than females who tend to be more concerned about their physical appearance and esthetic (10) , the same finding was reported by previous Iraqi studies (13,14) .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This could be explained by; gingivitis is the disease of children and its severity increase with age [4]. Children with traumatized teeth formed 20.8% and this was higher than many studies [18,19] but it lower than other studies [20,21]. Males demanded treatments for traumatized teeth more than females, this could be attributed to the fact that; males tend to be more active and participate in outdoor activities while females tend to be more mature in their behavior more stable and calmness than males.…”
Section: Discussionmentioning
confidence: 99%